Cyberbullying Involvement, Resilient Coping, and Loneliness of Adolescents During Covid-19 in Rural China - Han, Ziqiang; Wang, Ziyi; Li, Yuhuan (Frontiers in Psychology, 2021)
Cyberbullying involvement can lead to internal health issues, especially mental health problems. Different coping strategies may reduce or enhance the strengths between cyberbullying experience and mental health problems. In this study, we examined the correlations between cyberbullying involvement and feeling of loneliness among a group of children and adolescents during the Covid-19 pandemic in China, focusing on investigating the resilient coping strategy's protecting effect. The results demonstrated that 86.68% of the students were not involved in cyberbullying activities, 8.19% were victims only, 1.89% were perpetrators only, and 3.24% were both victims and perpetrators. Compared with the non-involved, the victims only had a significant higher degree of reported loneliness and a lower score of resilient coping, while the other groups’ difference were not significant. Resilient coping strategy can reduce the feeling of loneliness significantly and played a mediating role between the cyberbullying victimization and loneliness, but such mitigating effect was relatively weak. Besides, peer relations were the primary protective factors and age was the primary risk factor of loneliness among the controlled variables. This study can enrich current knowledge of cyberbullying involvement and the psychological health among children and adolescents, especially in the context of pandemics.